Development of employee attendance management system using flutter / Muhamad Faiz Akmal Mohamad Noor, Alif Faisal Ibrahim and Muhammad Nabil Fikri Jamaluddin - Akmal Mohamad, Muhamad Faiz; Ibrahim, Alif Faisal; Jamaluddin, Muhammad Nabil Fikri (UiTM Cawangan Perlis, 2023)
The workforce constitutes a fundamental element of organisations, and effectively addressing the challenges associated with governing employees is crucial for maintaining the overall stability of the firm. In the past, businesses and organisations used to depend on manual attendance tracking systems within their human resources departments to manage their staff. In the contemporary era characterised by significant advancements in technology, several recommendations are put out to enhance the existing system. Nevertheless, it is possible that small enterprises may encounter difficulties in coping with the escalating living expenses and the expenses associated with implementing an advanced attendance management system. Hence, this study proposes the creation of a straightforward yet dependable mobile application for the purpose of documenting and overseeing staff attendance through the utilisation of Flutter. The application was developed in a series of incremental steps utilising the Waterfall methodology. The effectiveness and acceptance of the application were evaluated using a comprehensive testing process that included both functionality and usability testing. Both testing findings yielded favourable outcomes, indicating that the application was favourably received by the responders. The application is anticipated to provide assistance to small enterprises or organisations that have encountered challenges in managing their operating expenses.